HUBUNGAN PERAN PENDAMPINGAN SUAMI DENGAN TINGKAT KECEMASAN PASIEN PRE OPERASI SECTIO CAESAREA DI RSU AMIRA, PURWAKARTA - Marlina, Ina; Afrina, Rina; Shifa, Nurul Ainul (Tirtayasa Medical Journal, 2025)
Preoperative anxiety is a common problem experienced by patients who will undergo surgical procedures, including Sectio Caesarea. This anxiety can have a negative impact on the physical and psychological condition of the patient. The role of husband's assistance is considered to provide a significant emotional and psychological role for patients. This study aims to determine the relationship between the role of husband's assistance and the level of anxiety of preoperative patients with sectio caesarea in the obstetrics room on the 2nd floor of Amira Hospital, Purwakarta in 2024. This study used a descriptive correlation design with a cross-sectional approach. The sample of this study was 50 patients who were going to undergo section caesarea surgery and met the inclusion criteria. Data were collected through the questionnaire on the role of husband's assistance and STAI. The results showed that there was a significant relationship between the role of husband's assistance and the level of anxiety of preoperative patients with sectio caesarea (r = -0.68, p <0.05. The role of husband's assistance has a significant relationship in reducing the level of anxiety of preoperative patients with sectio caesarea.